Bioconcentration of hexavalent chromium in different organs and induction of micronuclei in peripheral blood cells of Cirrhinus mrigala (Ham, 1822) - MALLESH, B; PANDEY, P K; KUMAR, KUNDAN; VENNILA, A; SHUKLA, S P; RAMAN, R P; KUMAR, SAURAV (The Indian Journal of Animal Sciences, 2015)
The fingerlings of Cirrhinus mrigala (Ham, 1822) were exposed to different concentrations of chromium in the form of K2Cr2O7. LC50 for 96 h was calculated as 52.187 mg L–1. For sub-lethal toxicity test fishes were exposed to different concentrations of 10.437, 5.218 and 3.479 mg L–1 for 60 days. In comparison to control under the same conditions, the experimental fish showed remarkable change in the accumulation pattern in muscle, gills and liver. The Cr content was measured and the highest concentration was found in liver (61.91±0.73 μg g–1) followed by gills (16.67±0.08 μg g–1) and muscle (8.97±0.06 μg g–1). Frequencies of micronuclei were evaluated in peripheral blood erythrocytes. Cells showed differential sensitivity to the heavy metal treatment. In general, frequencies of MNi cells significantly increased following the exposure for 60 days to chromium. Frequencies of micronuclei formation in erythrocytes varied from 0.83±0.06% to 6.37±0.56%. The results indicated that this heavy metal has genotoxic effects in the fish.